2022
DOI: 10.1186/s41182-022-00466-9
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication and Anti-malarial Drug Resistance in the Democratic Republic of the Congo (DRC): A silent threat

Abstract: Background Malaria is a global infectious (vector-borne: Anopheles mosquitoes) disease which is a leading cause of morbidity and mortality in Sub-Saharan Africa (SSA). Among all its parasitic (protozoan: Plasmodium sp.) variants, Plasmodium falciparum (PF) is the most virulent and responsible for above 90% of global malaria deaths hence making it a global public health threat. Main context Despite current front-line antimalarial treatments options … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…Anti-malarial self-medication among malaria symptomatic patients seeking treatment in hospitals was commonly encountered by the healthcare personnel. This is like reports from other studies that have found high prevalence of self-medication using anti-malarial agents in malaria affected regions [ 13 , 14 ]. Despite being prescription-only medicines, anti-malarial agents are accessed over the counter especially in most malaria affected countries.…”
Section: Discussionsupporting
confidence: 90%
“…Anti-malarial self-medication among malaria symptomatic patients seeking treatment in hospitals was commonly encountered by the healthcare personnel. This is like reports from other studies that have found high prevalence of self-medication using anti-malarial agents in malaria affected regions [ 13 , 14 ]. Despite being prescription-only medicines, anti-malarial agents are accessed over the counter especially in most malaria affected countries.…”
Section: Discussionsupporting
confidence: 90%
“…Antimalarial self-medication among malaria symptomatic patients seeking treatment in hospitals was commonly encountered by the healthcare personnel. This is like reports from other studies that have found high prevalence of self-medication using antimalarial agents in malaria affected regions [13,14]. Despite being prescription only medicines, antimalarial agents are accessed over the counter especially in most malaria affected countries.…”
Section: Discussionsupporting
confidence: 87%
“…Despite being prescription only medicines, antimalarial agents are accessed over the counter especially in most malaria affected countries. Self-treatment is likely to lead to delay in accessing appropriate treatment thus worsening of the disease which potentially leads to wasting of more resources and increased risk of morbidity and mortality [13]. The inability of healthcare personnel to con rm prior use of antimalarial agents among malaria symptomatic patients seeking treatment in hospitals further affects monitoring of self-medication in the country.…”
Section: Discussionmentioning
confidence: 99%
“…The great majority of cases are caused by P. falciparum and P. vivax. Plasmodium falciparum malaria, for example, is responsible for more than 90% of malaria cases and almost all malaria fatalities globally [2].…”
Section: Introductionmentioning
confidence: 99%